Comparison of Profitability and Activity Ratios in Healthcare Companies Listed on IDX Before, During, and After COVID-19 - Ii Ratna Sari; Santi Nur Wahyuni; Maiyaliza Maiyaliza (Universitas KH. Abdul Chalim Mojokerto, 2025)
At the beginning of 2020, the Covid-19 pandemic began to spread across various regions in Indonesia, causing many companies to experience various operational and financial impacts, especially health sector companies listed on the Indonesia Stock Exchange (IDX). Since the outbreak, the demand for health services has skyrocketed. Many people were infected with the virus, leading to a surge in patients at hospitals and healthcare providers, particularly those requiring intensive care due to COVID-19 infection. As a result, healthcare companies experienced changes in revenue and operational costs. The Net Profit Margin (NPM) ratio did not show substantial changes in the financial performance of healthcare companies before, during, and after the COVID-19 epidemic. The TATO ratio did not show substantial changes in the financial performance of healthcare companies before, during, and after the COVID-19 epidemic. Healthcare companies should improve operational efficiency and asset utilization to maximize revenue contributions and enhance operational management, enabling them to manage and allocate company assets more productively.